Mechanical Interaction of the Pericardium and Cardiac Function in the Normal and Hypertensive Rat Heart - Mendiola, Emilio A.; Sacks, Michael S.; Avazmohammadi, Reza (Frontiers in Physiology, 2022)
The pericardium is a thin connective tissue membrane that surrounds the heart and is an integral regulatory component of cardiopulmonary performance. Pathological growth and remodeling of the right ventricle (RV) stemming from structural heart diseases are thought to include a significant role of the pericardium, but its exact role remains unclear. The objective of this study was to investigate potential biomechanical adaptations of pericardium in response to pulmonary hypertension and their effects on heart behavior. Integrated computational-experimental modeling of the heart offers a robust platform to achieve this objective. We built upon our recently developed high-fidelity finite-element models of healthy and hypertensive rodent hearts via addition of the pericardial sac. In-silico experiments were performed to investigate changes in pericardium reserve elasticity and their effects on cardiac function in hypertensive hearts. Our results suggested that contractile forces would need to increase in the RV and decrease in the LV in the hypertensive heart to compensate for reductions in pericardium reserve elasticity. Discrepancies between chamber responses to pericardium addition result, in part, from differences in the impact of pericardium on ventricle preload. We further demonstrated the capability of our platform to predict the effect of pericardiectomy on heart function. Consistent with previous results, the effect of pericardiectomy on the chamber pressure-volume loop was the largest in the hypertensive RV. These insights are expected to motivate further computational investigations of the effect of pericardiectomy on cardiac function which remains an important factor in surgical planning of constrictive pericarditis and coronary artery bypass grafting.